2013
DOI: 10.1111/nmo.12261
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin increases vagally mediated gastric activity by central sites of action

Abstract: Background Vagally dependent gastric reflexes are mediated through vagal afferent fibers synapsing upon neurons of the nucleus tractus solitarius (NTS) which, in turn modulate the preganglionic parasympathetic dorsal motor nucleus of the vagus (DMV) neurons within the medullary dorsal vagal complex (DVC). The expression and transport of ghrelin receptors has been documented for the afferent vagus nerve, and functional studies have confirmed that vagal pathways are integral to ghrelin-induced stimulation of gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 58 publications
2
43
1
3
Order By: Relevance
“…Suppression of NTS‐CC neurons leads to inhibition of the DMV‐C‐i and disinhibition of DMV‐C‐e neurons. Ghrelin also disinhibits DMV‐C‐e neurons by activating AP‐GABA neurons and facilitates excitatory transmission to DMV‐C‐e neurons . Moreover, ghrelin also directly stimulates MY‐C‐e neurons.…”
Section: Gastric “Accelerating” Hormonesmentioning
confidence: 99%
See 1 more Smart Citation
“…Suppression of NTS‐CC neurons leads to inhibition of the DMV‐C‐i and disinhibition of DMV‐C‐e neurons. Ghrelin also disinhibits DMV‐C‐e neurons by activating AP‐GABA neurons and facilitates excitatory transmission to DMV‐C‐e neurons . Moreover, ghrelin also directly stimulates MY‐C‐e neurons.…”
Section: Gastric “Accelerating” Hormonesmentioning
confidence: 99%
“…In vivo, ghrelin increases gastric myoelectrical activity and gastric emptying in the rats . Ghrelin activates phase II activity in the antrum of the fasting stomach by a central action . The peripheral action of ghrelin facilitates motilin to induce the activity in front of the MMC .…”
Section: Gastric “Accelerating” Hormonesmentioning
confidence: 99%
“…In humans, ghrelin regulates some functions that depend on the activity of the autonomic nervous system; for instance, ghrelin increases gastric emptying and decreases blood pressure [28,29,30]. GHSR-1a is expressed in all three components of the dorsal vagal complex, and central administration of ghrelin to rodents recapitulates some of these actions of the hormone [31,32,33]; however, the extent to which these effects of ghrelin depend on its action at central level in humans is currently uncertain. Finally, it is interesting to stress that studies in rodents have shown that ghrelin system also impacts on higher cognitive functions, such as learning and memory, but the implications of these studies in humans are currently unclear [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, ghrelin inhibits ischemia/reperfusion-induced mucosal lesions given i.c.v., but increases gastric acid secretion in the same dose range [22]. Moreover, ghrelin injected into the IVth ventricle or into the DVC elicited contractions of the gastric corpus via excitation of a vagal cholinergic efferent pathway [37], however, ghrelin-induced gastroprotective effect was not reduced in higher dose range. The above data suggest the lack of a definitive correlation between the declined gastroprotective effect and the increased gastric acid secretion or gastric motor activity.…”
Section: Dose-reponse Relationshipsmentioning
confidence: 98%